PRODUCTIVE ZAKAT, INFORMATION TECHNOLOGY, AND MUSTAHIQ EMPOWERMENT: THE MODERATING ROLE OF ENTREPRENEURIAL MOTIVATION - Wiwin Sultraeni; Nasruddin Suyuti; Dian Mayafaty Rauf; Ilham Akbar Garusu; Ahmad Hamid (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2026)
mustahiq empowerment as well as investigates the moderating effect of entrepreneurial motivation on mustahiq of the National Amil Zakat Agency (BAZNAS) in Kendari. An explanatory sequential mixed-method approach was used in the study. For the quantitative part, a survey was conducted among 110 mustahiq who were engaged in productive zakat programs for the year 2024–2025. Data analysis was performed by using Partial Least Squares Structural Equation Modeling (PLS-SEM) technique and SmartPLS. It is revealed that productive zakat and information technology have significant positive impacts on mustahiq empowerment, direct and indirect through entrepreneurial motivation. Besides, entrepreneurial motivation increases the positive influence of productive zakat and information technology on empowerment. In order to add more qualitative depth to the findings of the quantitative study, ten mustahiq were selected on purposeful sampling basis and interviewed. The interview results indicate that productive zakat helps in gaining business confidence and sustainability while information technology broadens market reach and improves efficiency in operations. Entrepreneurial motivation proves to be a vital driver that transforms financial and technological help into empowerment through making people resilient, confident, and entrepreneurial.